Analisis Kontrastif Struktur Bahasa Madura Dan Bahasa Arab - Azisi; Nurfaiza (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Contrastive analysis is a systematic study by comparing two languages ​​to identify similarities and differences between the two languages, whether synchronous or not, including syntactic, phonetic and morphemic elements. With the aim of finding some differences and similarities in the two languages ​​that are the object of study. It is recognized that this method has shortcomings in terms of its predictive assumptions in the world of foreign language teaching. Therefore, in applying linguistic analysis, researchers should use more than one method. In this way, it is hoped that there will be complementarity between the methods in the analysis process carried out. In the end, in responding to this, one is able to assess and determine whether or not to accept it academically and rationally on the importance or not of contrastive analysis, its relevance or not in the world of foreign language teaching. Keywords: Contrastive Analysis, Madura Language and Arabic.